Escherichia coli virulence genes detected in diarrheal samples of children from the Lambayeque region – Peru - Yacarini-Martínez, Antero Enrique (2019)
Objective: This study aimed to detect, by multiplex PCR, genes associated with virulence factors of Escherichia coli de isolated from diarrheal samples of children under 5 years of age. Materials and methods: A descriptive, cross-sectional, single-cohort study, in which diarrheal samples from children under five years of age collected from January 2014 to March 2015 were analyzed. Specific primers for detecting the genes of the six pathotypes that cause childhood diarrhea were used: daaD gene (diffusely adherent Escherichia coli - DAEC), aggR gene (Enteroaggregative Escherichia coli - EAEC), eaeA gene (enteropathogenic Escherichia coli - EPEC), stx gene (Shiga toxin-producing Escherichia coli - STEC), ipaH gene (Enteroinvasive Escherichia coli - EIEC) and st gene (Enterotoxigenic Escherichia coli - ETEC). Results: Virulence genes were found in 37.74 % ( 40/106) of the 106 Escherichia coli isolated strains. The 1-to 2-year-old age group was the most affected with these genes (48.6 %). Conclusions: The daaD gene of the DAEC pathotype showed the greatest distribution (16.98 %). The detection of specific virulence genes could help to treat an episode of acute childhood diarrhea in an appropriate and timely manner.